Spectrophotometric Procedure for Fast Reactor Advanced Coolant Manufacture Control; IOP Conference Series: Materials Science and Engineering; Vol. 112 : Fundamental Aspects of Rare-earth Elements Mining and Separation and Modern Materials Engineering (REES-2015) - Andrienko O. S.; Egorov N. B. Nikolai Borisovich; Zherin (Gerin) I. I. Ivan Ignatyevich; Indyk D. V. (2016, 2016)
Title screen